The commercialization instruments of innovations: empirical research on FMCG market - E. V. Arsenova (Real Economics Publishing House, 2018)
The research objective is in definition of the main tools participating in process of commercialization of grocery and marketing on the basis of expansion and deepening of the existing theory and methodology of commercialization, and also development of recommendations to improvement of tools that will promote finally to increase of efficiency of process of acceptance of a novelty by the market. Research is conducted on the basis of two-stage methodology including at the first stage carrying out questioning among the employees occupied in the course of commercialization in the large companies FMCG of the market, and at the second stage a case - research of two - players of the Russian market of juice. Confirmation of the made hypothesis that in most cases the innovations put on the market, can be considered grocery that is explainable that such innovations are capable to give to consumers essentially new advantages is result of research. The interrelation between stages of commercialization and the tools applied during this period is also confirmed. In the analysis of separate tools the tools informing the consumer on new products showed the greatest importance. Among them the special importance is played by TV advertizing. Practical application of results consists in identification tools for each of stages of commercialization of innovations the FMCG companies, and also those from them which play a paramount role on each of stages are defined.